Groups with Various Minimal Conditions on Subgroups - Dixon, M. R.; Evans, M. J.; Smith, H. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We briefly review some recent works on groups with the weak minimal condition on nonnilpotent subgroups. We also study the class of groups with the weak minimal condition on non-(soluble of derived length d) subgroups.